Evaluasi Penerapan Terapi MDT pada Kasus Kusta di Kota Lhokseumawe - Haur Syakira Radra; Yuziani Yuziani; Mohamad Mimbar Topik (Pusat riset dan Inovasi Nasional, 2025)
Leprosy is a chronic infectious disease caused by the bacterium Mycobacterium leprae. It is a neglected tropical disease, still found in more than 120 countries, with more than 200,000 new cases reported each year.. The purpose of this research is to characterize leprosy patients in Lhokseumawe City and to describe the Multi Drug Therapy therapy. Information about the therapy, including the kind of leprosy, age, gender, employment, and the precise period of treatment, is evaluated in this research. Instruments for measurement were derived using data collected from medical records in this cross-sectional observational investigation. A whole sampling population was used in the sampling procedure, with 42 respondents making up the sample. Based on these findings, MB leprosy is the most frequent form of the disease (90.5% of cases), men make up the majority (64.3%) of leprosy patients, and the majority of leprosy patients are adults (88.1%). Results from the MDT treatment protocol indicated that 76.2% of patients were considered to have finished therapy (RFT), with the biggest occupational category being patients who did not work, accounting for 50% of the total. It is imperative that leprosy officers work to promote health promotion in order to raise awareness, decrease negative stigma, and speed up the discovery of leprosy cases